EPIDEMIOLOGICAL FEATURES OF TUBERCULOSIS IN THE REPUBLIC OF KARAKALPAKSTAN IN THE PERIOD 2011-2020 (World Bulletin of Public Health, 2023)
It is known that tuberculosis (TB) is currently a serious burden on world health. As with any disease, much attention is paid to the morbidity of children. The article describes the peculiarities of the spread of TB, as well as the epidemiological characteristics of the territorial distribution of the primary incidence of this infection. Dynamics of incidents (intensive indicators) TB per 100 thousand population for the period 2011-2020 has a downward trend. Thanks to the consistent fight against TB, it was possible to achieve a steady decrease in morbidity rates both in Uzbekistan and in the Republic of Karakalpakstan